Semantic density: A translation device for revealing complexity of knowledge practices in discourse, part 1—wording - Maton, Karl; Doran, Y. J. (Onomázein, 2017)
In education research ‘complexity’ is often viewed cognitively as a mental attribute and so the complexity of knowledge practices themselves remains underexplored. Legitimation Code Theory conceptualizes such complexity as ‘semantic density’, which describes how mea-nings are condensed and interrelated within knowledge practices. This concept is becoming widely enacted in education as a means of identifying and teaching highly-valued practices. As yet, how ‘semantic density’ could be enacted to analyse the discourse of actors remains uncertain. This paper is the first of two articles that introduce a means of enacting the con-cept in analysis of English discourse. Together they offer a ‘translation device’ that explores discourse for signs of the complexity of the knowledge being expressed. This first paper intro-duces tools for exploring how the wording used by actors realizes different strengths of ‘epis-temic-semantic density’, where meanings are empirical descriptions or formal definitions. It provides typologies for identifying different kinds of wording and describes how these types manifest different degrees of complexity. Two contrasting examples, from a secondary school History classroom and a scientific research article, are analysed to illustrate the insights into complexity offered by these tools. In the second paper we build on these ideas with tools for analysing how words are combined to generate different degrees of increasing complexity, to enable a fuller understanding of knowledge-building